Decreased keratinocyte Proline‐Rich protein expression in cutaneous T‐cell lymphoma - Teruyoshi Hisamoto; Hiraku Suga; Issey Omori; Yuka Mizuno; Kenta Oka; Hikari Boki; Naomi Takahashi‐Shishido; Tomonori Oka; Tomomitsu Miyagaki; Makoto Sugaya; Shinichi Sato (Frontiers Media S.A., 2022)
Abstract Background Cutaneous T‐cell lymphomas (CTCLs) often have skin dryness and skin barrier dysfunctions, which are also seen in atopic dermatitis (AD). Expression of keratinocyte proline‐rich protein (KPRP) was decreased in the epidermis of AD, which led to barrier defects and further allergic inflammation. Objectives The aim of this study was to analyze KPRP expression in CTCL. Materials & Methods Skin samples of CTCL and healthy control were collected, and KPRP mRNA expression in the skin tissue was analyzed. We also performed immunohistochemistry of KPRP protein. Results Keratinocyte proline‐rich protein (KPRP) mRNA expression was decreased compared with normal skin. KPRP expression was positively correlated with that of filaggrin and loricrin, and it was negatively correlated with serum interleukin‐2 receptor levels. Immunohistochemistry staining showed that KPRP was detected in upper part of granular layer of epidermis in normal skin and in early‐stage CTCL, but rarely detected in the advanced‐stage CTCL. Conclusion In conclusion, we revealed the decrease in KPRP expression in CTCL.